PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PROBING PROMPTING UNTUK MENINGKATKAN SIKAP ILMIAH SISWA DI SMP NEGERI 7 TAMBANG KABUPATEN KAMPAR - Rauda Darmayanti; Azizahwati Azizahwati; M.Nor M.Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know the improvement of students' scientific attitude between after and before the implementation of cooperative learning model type probing Prompting on the Force material. The subject of this research is the students of class VIII SMP Negeri 7 Tambang Kampar regency, which consists of 25 students. Data in this research is primary data obtained from prestest and posttest score of student using questionnaire of scientific attitude of student then analyzed descriptively. Questionnaire student's scientific attitude consists of four indicators of curiosity, critical thinking, open thinking and honest. Based on data analysis, the score of attitude of scientific students beginning and end with high category. Then analyzed by using the gain where the students 'attitude of students' scientific attitude gained by 0,36 in the middle category. Thus, it can be concluded that cooperative learning model of Prompting probing type can improve students' scientific attitude toward middle category category.Keywords: Probing Prompting, Student's Scientific Attitude, force